Dinamika Agama Islam : Tantangan dan Transformasi dalam Konteks Kontemporer - Tasya Avionia; Syahidin Syahidin (Jurnal Budi Pekerti Agama Islam, 2024)
The dynamics of Islamic religion have become a significant focus of attention in the contemporary context, especially in the midst of rapid and complex global change. This article describes the challenges and transformations faced by the Islamic Religion in facing contemporary realities. In an ever-changing world, religions are often faced with various pressures and dynamics that influence the way their followers understand and practice their religious teachings. The challenges faced by the Islamic Religion include issues such as modernization, globalization, pluralism and radicalization. Modernization brings changes in the way individuals understand and practice their religion, while globalization introduces various views and values ​​from various cultures that influence Islamic identity globally. Pluralism raises questions about how Islam interacts with other religions and maintains tolerance between religious believers, while radicalization poses challenges to moderate understanding of religion and peace.